Improving Employee Performance through the Influence of Organizational Justice, Job Satisfaction, and Organizational Commitment (A Study at the Population and Civil Registration Office of Manokwari Regency) - Mince Sampebunga; Budiman Budiman (Green Publisher Indonesia, 2024)
This research aims to analyze strategies for improving the performance of Manokwari Regency Population and Civil Registration Service employees through the influence of Organizational Justice, Job Satisfaction and Organizational Commitment. This research uses a quantitative approach with analytical survey methods. The data used is primary data obtained from distributing questionnaires to the entire population of 50 people. The analytical method used in this research is inferential statistics using multiple linear regression analysis tools using SPSS 21 software. The results of the research show that Organizational Justice, Job Satisfaction and Organizational Commitment can have a positive and significant effect, partially or simultaneously, on the performance of employees in the service. Population and Civil Registration of Manokwari Regency.